Ultrasonographic characteristics of the testes, epididymis and accessory sex glands and arterial spectral indices in peri- and post-pubertal Nelore and Caracu bulls - Rodrigues, Naiara Nantes [UNESP]; Rossi, Guilherme Fazan [UNESP]; Vrisman, Dayane Priscila [UNESP]; Taira, Augusto Ryonosuke [UNESP]; Souza, Luana Lelis; Zorzetto, Mariana Furtado; Bastos, Natalia Marins [UNESP]; Paro de Paz, Claudia Cristina; Martins Hossepian de Lima, Vera Fernanda [UNESP]; Monteiro, Fabio Morato; Franco Oliveira, Maria Emilia [UNESP] (Elsevier B.V., 2020)
Ultrasonography can provide information about the integrity of organs; however, rarely is applied to the reproductive organ evaluation of bulls. The objective of the present study was to characterize and compare values for variables and ultrasonographic characteristics of the testes, epididymis and accessory sex glands, as well as spectral Doppler indices of the testicular and internal iliac arteries, between peri- and post-pubertal Nelore and Caracu bulls. Nelore (n = 203) and Caracu (n = 79) bulls were assigned by age class: peri-pubertal (12-15 months) and postpubertal ( > 22 months). Data were analyzed using SAS's PROC MIXED procedure (P < 0.05). The biometric variables of the testes and cauda epididymis differed between peri- and postpubertal Nelore and Caracu bulls. There was a difference between breeds for the vesicular glands, ampulla of vas deferens, disseminate portion of the prostate, and craniocaudal dimension of the bulbourethral glands. Echogenicity of the testicular parenchyma differed between breeds and age classes. The pulsatility and resistive indices of the testicular arteries differed between Nelore and Caracu bulls. The biometric and ultrasonographic characteristics of the testes, epididymis and accessory sex glands, as well as of the arterial indices in bulls are affected by genetic group and age class, and when assessed there is useful information regarding the progression of sexual maturation.
Keywords: Andrological; Bovine; Echogenicity; Echotexture; Vascular indices